Large Gas Reservoir Along the Rift Axis of a Continental Back‐Arc Basin Revealed by Automated Seismic Velocity Analysis in the Okinawa Trough. Issue 16 (30th August 2019) - Mukumoto, Kota; Tsuji, Takeshi; Hendriyana, Andri
Abstract: In the Okinawa Trough off southwestern Japan, hydrothermal circulation due to back‐arc rifting is active. Biogenic CH4 in discharging hydrothermal fluids at the Iheya North Knoll is derived from outside the knoll; however, the location of the gas reservoir has not been identified. Here, we applied automated velocity analysis to seismic reflection data to obtain a P wave velocity structure in high spatial resolution. The resulting profiles reveal large gas reservoirs as low‐velocity zones along the rifting axis (>5 km for axis direction) around the Iheya North Knoll. The main gaseous components in the reservoir could be CO2 and CH4 . The heat flow inferred from seismic profiles (i.e., depth of reflector) indicates that CH4 hydrate could be trapping the gas. Furthermore, the heat flow is higher at the rifting axis and close to the knoll, reflecting the large gas reservoir feeding the hydrothermal fluids in the discharging area at the knoll. Plain Language Summary: Magmatic activity in the middle Okinawa Trough region southwest of Japan gives rise to intense hydrothermal activity. Gases in the hot fluids discharging from the hydrothermal field at Iheya North Knoll consist mainly of biogenic CH4 originating from microbial activity and CO2 . By applying high‐resolution automated velocity analysis to seismic reflection data, this study revealed widely distributed gas reservoirs as inferred from their low seismic velocities. Furthermore, our estimates of heat flow suggest that these gas reservoirs are capped by CH4 hydrate. If the main gas component is CH4, the gas reservoir may be a potential natural resource. If the gas includes CO2, the distribution of similar reservoirs is important because CO2 is the main contributor to global warming. Key Points: High‐resolution P wave velocities in the middle Okinawa Trough demonstrate existence of large‐scale gas reservoir at the rifting axis Widespread gas reservoirs trapped by hydrates could influence hydrothermal fluids in the discharging area at Iheya North Knoll Estimated heat flow is higher at the rifting axis and close to Iheya North Knoll, reflecting the presence of hydrothermal systems